Perbedaan Makna Bahasa Tulis dan Bahasa Lisan - Edi Syahputra; Fadlan Fadlan; Dandi Salmanda; Kezia Nur Elizanti Purba (Universitas Dehasen Bengkulu, 2022)
Nowadays, the digital world has become part of daily lives of Indonesian people , especially in sending messages to someone and it is proven by advancement of the digital world which makes it easier for people to communicative via telephone or applications such as: WhatsApp, Instagram, Messenger, etc. However, because the convenience is getting better, we often find people who has difficulty in speaking orally. The purpose of our research is to find the difference between written language and spoken language with method we use to achieve and find which language is better to use in Indonesia.